Предмет: Алгебра,
автор: lobanov123
Упростите:
Спасибо!
Ответы
Автор ответа:
0
Автор ответа:
0
9*(2x-3)-9x(x+3)+x^2(x+12) / 9x^2 *3x/(9-x^2) =
= (18x-27-9x^2-27x+x^3+12x^2) / 3x *1/(9-x^2) =
= (x^3+3x^2-9x-27) / 3x *1/(9-x^2) =
= x^2(x+3)-9(x+3) /3x * -1/(x^2-9)=
=(x+3)(x^2-9) /3x * -1/(x^2-9)= - (x+3)/3x
= (18x-27-9x^2-27x+x^3+12x^2) / 3x *1/(9-x^2) =
= (x^3+3x^2-9x-27) / 3x *1/(9-x^2) =
= x^2(x+3)-9(x+3) /3x * -1/(x^2-9)=
=(x+3)(x^2-9) /3x * -1/(x^2-9)= - (x+3)/3x
Похожие вопросы
Предмет: География,
автор: Аноним
Предмет: Математика,
автор: mashaloian
Предмет: Литература,
автор: vladmekson0322
Предмет: Алгебра,
автор: Тёма87